BRAID GROUP REPRESENTATION ON QUANTUM COMPUTATION - Kasyfil Aziz, Ryan
There are many studies about topological representation of quantum computation recently. One of diagram representation of quantum computation is by using ZXCalculus. We will make a diagrammatical scheme of Quantum Teleportation and Dense Coding. Furthermore, we will prove that ZX-Calculus diagram of maximally entangle state satisfies Yang-Baxter Equation. Therefore, we can construct a Braid Group representation on quantum computation.